Factors Affecting the Intention to Continue Using Online Payment Applications of SMEs at Viet Nam - NGUYEN THI PHUONG, Giang; THAI DONG, Tan; NGUYEN BINH PHUONG, Duy; LE HUU, Hung; LE THI HONG, Nhung (Theoretical and Practical Research in Economic Fields; Vol 15 No 4 (2024): TPREF Volume XV, Issue 4(32), Winter 2024, 2024)
This study aims to identify the factors influencing the intention to continue using online payment applications among small and medium enterprises (SMEs) in Vietnam. The research employs a mixed-methods approach, combining qualitative and quantitative techniques. A theoretical framework was developed based on existing studies, which was subsequently refined to suit the context of SMEs in Vietnam. Data were collected through a Google Forms survey targeting 388 businesses familiar with online payment technologies such as Banking, Momo, Zalo Pay, AirPay, and ViettelPay. The data were analyzed using Smart PLS 4 software. Findings: The analysis reveals six key factors affecting the intention to continue using online payment applications: privacy security, social influence, perceived risk, perceived usefulness, information technology knowledge, and trust. This study contributes to the limited body of research focusing on SMEs in Vietnam and their adoption of online payment technologies. It provides a context-specific evaluation of factors driving continued usage intentions, offering insights for both academia and practice. The study is limited to SMEs in Vietnam, which may affect the generalizability of the findings to other contexts. Future research could explore these factors across different industries or regions. The study offers management strategies for enhancing SMEs’ trust and perceived usefulness of online payment technologies, ultimately fostering continued adoption. The findings can contribute to the broader adoption of digital payment systems, promoting a cashless society and improving economic efficiency in Vietnam.